Pure natural orifice transluminal endoscopic surgery (NOTES) involving peroral endoscopic salpingo‐oophorectomy (POESY). Issue 1 (2nd January 2014) - Hornemann, Amadeus; Suetterlin, Marc; Trunk, Marcus J.; Gerhardt, Axel; Kaehler, Georg
Abstract: Objective: Natural orifice transluminal endoscopic surgery (NOTES) is a surgical approach that uses natural orifices to gain access to areas of the body. In the present article, we describe the first transgastric pure NOTES salpingo‐oophorectomy, which we call peroral endoscopic salpingo‐oophorectomy (POESY). Methods: A woman with BRCA1 mutation presented for prophylactic bilateral salpingo‐oophorectomy. We offered her the transgastric approach, having performed more than 25 transgastric appendectomies. After gastroscopic incision in the corpus wall, we advanced the gastroscope into the abdominal cavity. Salpingo‐oophorectomy was performed with the help of an intrauterine manipulator and a transvaginally introduced 5‐mm trocar. The posterior colpotomy was dilated and the specimens were extracted. The gastrotomy was closed with an over‐the‐scope clip, and the colpotomy with a running suture. Results: The gastroscope provided excellent optical control and good tissue preparation. Prophylactic bilateral salpingo‐oophorectomy was performed successfully via POESY. The patient recovered quickly and was discharged on the third day, with an uneventful follow‐up. Conclusion: The present case demonstrates the feasibility of transgastric access. The gastroscope provided excellent optical control and good tissue preparation. Therefore, we expect an increasing role of transgastric procedures for diseases in the pelvic region, particularly if new endoscopic platforms with better means of instrumentation and tissue management become available.